Construção do espaço urbano da pequena cidade: um estudo sobre São Sepé - RS - Scherer, Fabiano Bolzan (2009)
The present dissertation is an analysis in its spatial and temporal scales and the roles of urban land use in the small town of São Sepé in which dynamic is related to the agricultural sector in which the city is part. Therefore, there are many roles in the economic sector, specifically associated to the cooperative named COTRISEL. The reality of this town is expressed by economic flows from the business generated by the cooperative in the region. In this context, this town of Portuguese colonization, the concession the Sesmarias (large land properties), for many centuries it was dominated by elites, owners of land, defending their interests. The economy of São Sepé focuses on the agricultural sector, with trading and services depending on this sector. It is also the agribusiness benefit from the primary production, adding that production value. It was also analyzed, the capital, the urban equipment and infrastructure in order to verify how this type of economy was able to generate jobs, equipment or even urban infrastructure to conduct activities.